Applications of Three-Dimensional Printing in the Production of Cultured and Plant-Based Meat: Review Article (Journal of Pharma Insights and Research, 2025)
Three-dimensional printing (3DP) technology represents a revolutionary advancement in food production, particularly in the meat industry. This emerging technology enables the creation of customized meat products with enhanced nutritional profiles and optimized sensory characteristics. The process involves either cultivating animal cells in bioreactors to produce bio-ink or utilizing plant-based protein formulations to create meat alternatives. The bio-ink or plant protein matrix is then extruded through specialized nozzles in a layer-by-layer approach, following computer-aided design patterns to achieve desired structural properties. Recent developments in 3DP technology have focused on improving the rheological properties of printing materials, maintaining precise temperature control during extrusion, and developing multi-material printing capabilities. The technology addresses several critical challenges in conventional meat production, including sustainability, customization of nutritional content, and reduction of food waste. Temperature-controlled extrusion systems with multiple printing heads have demonstrated success in maintaining product safety while achieving complex internal architectures. Significant progress has been made in optimizing cell culture conditions, developing suitable growth media, and enhancing the structural integrity of printed products. The integration of various preprocessing and post-processing techniques has improved the final product's texture, flavor, and stability